2014
DOI: 10.1021/la5008389
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and Correlating Solubility Parameters Governing the Self-Assembly of Molecular Gels Using 1,3:2,4-Dibenzylidene Sorbitol as the Gelator

Abstract: Solvent properties play a central role in mediating the aggregation and self-assembly of molecular gelators and their growth into fibers. Numerous attempts have been made to correlate the solubility parameters of solvents and gelation abilities of molecular gelators, but a comprehensive comparison of the most important parameters has yet to appear. Here, the degree to which partition coefficients (log P), Henry’s law constants (HLC), dipole moments, static relative permittivities (εr), solvatochromic ET(30) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 63 publications
(237 reference statements)
3
116
0
Order By: Relevance
“…In that regard, attempts to correlate the E T (30) scale44 and systems involving 9,12 R ‐diol, trans ‐9,10‐diol, and trans ‐13,14‐diol were unsuccessful (Figure S11 in the Supporting Information). The inability of E T (30) to predict the formation of gels within the diol gelators implies that bulk polarity is an insufficient criterion to judge when a gel will or will not be formed;3a specific liquid–gelator interactions at the molecular level must be considered as well.…”
Section: Resultsmentioning
confidence: 99%
“…In that regard, attempts to correlate the E T (30) scale44 and systems involving 9,12 R ‐diol, trans ‐9,10‐diol, and trans ‐13,14‐diol were unsuccessful (Figure S11 in the Supporting Information). The inability of E T (30) to predict the formation of gels within the diol gelators implies that bulk polarity is an insufficient criterion to judge when a gel will or will not be formed;3a specific liquid–gelator interactions at the molecular level must be considered as well.…”
Section: Resultsmentioning
confidence: 99%
“…54 They found that individual HSPs, especially the hydrogen bonding HSP (d h ), strongly influence the physical properties of the DBS organogel -much more so than solvent polarity. 54 They found that individual HSPs, especially the hydrogen bonding HSP (d h ), strongly influence the physical properties of the DBS organogel -much more so than solvent polarity.…”
Section: Systematic Studies Of Solvent Effects On Dbs Gelationmentioning
confidence: 99%
“…This is due to their importance for understanding the origin of the driving force for the unique architectural features, to encourage intriguing new forms of gelation behavior, as well as for developing efficient supramolecular gelators. [5][6][7] A wide variety of research articles have tried to understand the mechanism of the self-assembly process from different point of views. 4 However, the mechanisms governing the self-assembly of a number of supramolecular nanostructures, including supramolecular gels, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%